Trace amounts of African swine fever virus DNA detected in insects collected from an infected pig farm in Estonia. Issue 1 (27th September 2019) - Herm, Reet; Tummeleht, Lea; Jürison, Margret; Vilem, Annika; Viltrop, Arvo
Abstract: Background: African swine fever (ASF), a severe multi‐systemic disease in pigs, was introduced into Estonia in 2014. The majority of outbreaks have occurred during the summer months. Given that ASFV is transmitted in a sylvatic cycle that includes the transmission by African soft ticks and that mechanical transmission by flying insects was shown, transmission by other arthropod vectors need to be considered. Objectives: Here, we report the results of a pilot study on flying insects caught on an outbreak farm during epidemiological investigations. Methods: In brief, 15 different insect species (flies and mosquitoes) were collected by random catch using an aerial net. Nucleic acids derived from these samples or their pools were tested for African swine fever virus (ASFV) DNA by real‐time PCR. Results and Conclusions: Viral DNA was detected in small quantities in two samples from flies and mosquitoes. Given the slow spread of virus within the farm, the impact of these findings seems rather low, but a role in local transmission cannot be ruled out. However, given the very low number of insects sampled, and taken into the account that viral isolation was not performed and insects outside the farm were not investigated, future investigations are needed to assess the true impact of insects as mechanical vectors. Abstract : Flying insects collected in a pig farm affected by African swine fever were analysed for the presence of viral DNA using real‐time PCR method. Trace amounts of African swine fever DNA was discovered in a small number of insects.